Tanggung Jawab Pengendali Data Dalam Memberikan Pelindungan Data Pribadi Anak di Indonesia: Studi Komparasi Negara Inggris - Nabila Ishma Nurhabibah; Sinta Dewi Rosadi; Fatmi Utarie Nasution (MORALITY: Jurnal Ilmu Hukum, 2023)
Privacy protection as a fundamental right of society is one of the crucial legal aspects in the midst of current information technology developments. In fact, children also have privacy rights that must be protected. The purpose of this study is to identify and analyze the responsibilities of data controllers in providing personal data protection for children in Indonesia with a comparison to English law. The method used in this research is juridical-normative. The result of this research is that the condition for granting parental consent as the only indicator for assessing child data protection in the Personal Data Protection Act in Indonesia can imply a reduction in the responsibility of the data controller in providing personal data protection. Responsibility for protecting children's personal data must also include responsibility for data controllers by considering the fulfillment of children's rights and the best interests of children.